2013
DOI: 10.1038/cgt.2013.28
|View full text |Cite
|
Sign up to set email alerts
|

A triple suicide gene strategy that improves therapeutic effects and incorporates multimodality molecular imaging for monitoring gene functions

Abstract: Gene-directed enzyme prodrug therapy (GDEPT), or suicide gene therapy, has shown promise in clinical trials. In this preclinical study using stable cell lines and xenograft tumor models, we show that a triple-suicide-gene GDEPT approach produce enhanced therapeutic efficacy over previous methods. Importantly all the three genes (thymidine kinase, cytosine deaminase, and uracil phosphoribosyltransferase) function simultaneously as effectors for GDEPT and markers for multimodality molecular imaging (MMI), using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Furthermore, our studies demonstrated that hypoxia-targeted expression of bifunctional suicide gene CDUPRT enhanced the cytotoxicity of 5-FC treatments and radiosensitization under hypoxic conditions ( 15 ). We also found the superior antitumor effects of triple suicide gene approach-TKCDUPRT over double gene approach-TKCD in a rat prostate tumor model ( 16 ).…”
Section: Introductionmentioning
confidence: 80%
“…Furthermore, our studies demonstrated that hypoxia-targeted expression of bifunctional suicide gene CDUPRT enhanced the cytotoxicity of 5-FC treatments and radiosensitization under hypoxic conditions ( 15 ). We also found the superior antitumor effects of triple suicide gene approach-TKCDUPRT over double gene approach-TKCD in a rat prostate tumor model ( 16 ).…”
Section: Introductionmentioning
confidence: 80%
“…NMI and MR spectroscopy Gene-directed enzyme prodrug therapy has shown promise in clinical practice. Xing et al 152 designed a triple-suicide-gene (TK, cytosine deaminase [CD] and uracil phosphoribosyltransferase [UPRT]). As an effector, TK converts the prodrug GCV into toxic products.…”
Section: Preclinical Applications Of Multimodality Reporter Gene Imagmentioning
confidence: 99%
“…(E) Surviving fractions of TKCDUPRT (left panel) or TKCD (right panel) cells treated with different doses of GCV, 5-FC or GCV + 5-FC for 24 h. (F) Tumor growth kinetics in mice bearing TKCDUPRT tumors or TKCD tumors untreated or treated with different doses of GCV and 5-FC. (A-D adapted with permission from 152 , copyright 2013 Nature Publishing Group)…”
Section: Figurementioning
confidence: 99%